Chronic Stress Is Associated with Pain Precipitation and Elevation in DeltaFosb Expression - Wang, Hang; Tao, Xinrong; Huang, Si-Ting; Wu, Liang; Tang, Hui-Li; Song, Ying; Zhang, Gongliang; Zhang, Yong-Mei (Frontiers in Pharmacology, 2016)
A number of acute or repeated stimuli can induce expression of DeltaFosB (ΔFosB), a transcription factor derived from the fosB gene (an osteosarcoma viral oncogene) via alternative splicing. ΔFosB protein is currently viewed as a 'molecular switch' to repeated stimuli that gradually converts acute responses into relatively stable adaptations underlying long-term neural and behavioral plasticity. ΔFosB has received extensive attention in drug addition, depression and stress adaptation, but changes in ΔFosB protein expression during pain is not fully understood. In this study we explored ΔFosB expression in the medial prefrontal cortex (mPFC) of rats experiencing chronic or acute stress-induced pain. Our data reveal that chronic pain induced by neonatal colorectal distension, chronic constriction injury of the sciatic nerve, or maternal separation was associated with an increase in ΔfosB protein expression in mPFC, but acute application of acetic acid or zymosan did not alter the ΔFosB protein expression. ΔFosB expression in the rat visual cortex, a non pain-related brain region, did not change in response to chronic constriction injury of the sciatic nerve and acetic acid treatment. In conclusion, our results indicate that ΔFosB protein expression is significantly elevated in rats that have experienced chronic pain and stress, but not acute pain. The ΔFosB protein may serve as an important transcription factor for chronic stress-induced pain. Further research is needed to improve the understanding of both the upstream signaling leading to ΔFosB protein expression as well as the regulation of ΔFosB gene expression in cortical neurons.